Control of mRNA Translation in ALS Proteinopathy - Cestra, Gianluca; Rossi, Simona; Di Salvio, Michela; Cozzolino, Mauro (Frontiers in Molecular Neuroscience, 2017)
Cells robustly reprogram gene expression during stress generated by protein misfolding and aggregation. In this condition, cells assemble the bulk of mRNAs into translationally silent stress granules, while they sustain the translation of specific mRNAs coding for proteins that are needed to overcome cellular stress. Alterations of this process are deeply associated to neurodegeneration. This is the case of amyotrophic lateral sclerosis (ALS), a neurodegenerative disorder caused by a selective loss of motor neurons. Indeed, impairment of protein homeostasis as well as alterations of RNA metabolism are now recognized as major players in the pathogenesis of ALS. In particular, evidence shows that defective mRNA transport and translation are implicated. Here, we provide a review of what is currently known about altered mRNA translation in ALS and how this impacts on the ability of affected cells to cope with proteotoxic stress.